2004
DOI: 10.1111/j.1365-2273.2004.00864.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase of the apnoea-hypopnoea index after uvulopalatopharyngoplasty: analysis of failure1

Abstract: From 70 patients who had uvulopalatopharyngoplasty (UPPP) operation and a pre- and postoperative sleep registration, we could retrospectively determine the failures and the correlation between variables such as age, gender, body mass index (BMI), earlier or concomitant tonsillectomy, unilevel (uvula-palate-tonsil) or multilevel (base of tongue as well) obstruction during sleep endoscopy and treatment outcome. From 70 patients, the preoperative sleep registration classified 15 social unacceptable snorers and 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 18 publications
0
34
0
3
Order By: Relevance
“…The VOTE classification differs slightly from what we have developed independently for use in our practice [8,10,15,16] as it reflects the most fundamental aspects of the DISE evaluation. It does not prevent the addition of centerspecific assessments, but using a core classification and reporting the findings will advance our understanding of DISE, which has been limited to some extent by the wide diversity of systems in use around the world.…”
Section: Degree Of Airway Narrowingmentioning
confidence: 98%
See 1 more Smart Citation
“…The VOTE classification differs slightly from what we have developed independently for use in our practice [8,10,15,16] as it reflects the most fundamental aspects of the DISE evaluation. It does not prevent the addition of centerspecific assessments, but using a core classification and reporting the findings will advance our understanding of DISE, which has been limited to some extent by the wide diversity of systems in use around the world.…”
Section: Degree Of Airway Narrowingmentioning
confidence: 98%
“…Studies show that subjects with palatal obstruction alone (vs. multilevel obstruction) on DISE had better outcomes after palate surgery [9,10], and the resolution of airway obstruction with manual mandibular advancement under sedation is associated with improved outcomes with treatment using mandibular repositioning appliances [11,12]. However, in spite of over two decades of experience, important clinically relevant questions remain unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, surgical failure can result despite an apparently favorable preoperative anatomical milieu. 10 The crucial missing information is an understanding both of the dominant pathophysiological mechanisms responsible for airway obstruction in a given patient (particularly nonanatomical at baseline in responder versus nonresponder groups; ^post surgery in responder versus nonresponders. Independent samples t-test for parametric data, Mann-Whitney U for nonparametric unpaired data, Wilcoxon signed rank for nonparametric paired data.…”
Section: Selecting Patients For Upper Airway Surgerymentioning
confidence: 99%
“…Several investigators have previously attempted to use anthropomorphic, 3 polysomnographic (PSG), 4,5 and anatomical [6][7][8][9] factors to predict success, but each of these do not have sufficient accuracy to be applied in clinical practice. 10 As such, there is significant motivation to better understand the mechanistic factors that determine surgery success and, as a result, to develop methods which reliably predict the patients who will respond favorably to upper airway surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Multivariate logistic regression analysis revealed the presence of a complete circumferential collapse at the velum or a complete anteroposterior collapse at tongue base to be independent predictors of upper airway surgery failure. Earlier studies have shown that subjects with palatal obstruction alone versus multilevel obstruction on DISE had better outcomes after palate surgery [48,49].…”
Section: Dise: Findings In Relation To Clinical and Sleep Parameters mentioning
confidence: 99%